2004
DOI: 10.1103/physreve.70.036303
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear hydrodynamic waves: Effects of the equation of state

Abstract: The problem of the decay of an initial discontinuity (the Riemann problem) is studied for a substance with abnormal properties when the rarefaction waves get a shock form, whereas the compression waves become nonsharp with the width proportional to the distance traveled. Such a situation is inherent to matter in a near-critical thermodynamic state and is also met in many other physical systems. The behavior of pressure jumps is compared for the van der Waals equation of state and for its more realistic three-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Other work has shown that a single measurement of the density profile (as a function of distance) for an expanding 1D material can be used to infer the pressure as a function of density [20]. Previous work on hydrodynamic waves in generalized VDW fluids in the vicinity of the two-phase regime, but still above the critical point, showed the possible presence of rarefaction shockwaves, particularly for foils of finite thickness [12,[21][22][23]].…”
Section: Introductionmentioning
confidence: 99%
“…Other work has shown that a single measurement of the density profile (as a function of distance) for an expanding 1D material can be used to infer the pressure as a function of density [20]. Previous work on hydrodynamic waves in generalized VDW fluids in the vicinity of the two-phase regime, but still above the critical point, showed the possible presence of rarefaction shockwaves, particularly for foils of finite thickness [12,[21][22][23]].…”
Section: Introductionmentioning
confidence: 99%
“…the structure and properties of molecular liquids, liquid metals and crystals, their freezing and melting, and their critical behaviors [20]. With three degrees of freedom, the VDW EOS also corresponds to a monatomic gas at low density and does not yield rarefaction shockwaves [16,18,[21][22][23]. Nevertheless, the quantitative application of the VDW EOS must be checked and several directly measurable quantities can help us confirm, improve or reject the VDW model.…”
Section: Introductionmentioning
confidence: 99%